Readjustment of "Kalanganyar" Area as A Tourism Village With The Basis of Coastal Architecture Satellite Images Data - Elviana, Eva; F. Mutia; A. N. Yunisya (Nusantara Science and Technology Proceedings)
Coastal areas are seafront areas, which are a unique and dynamic part of the city that portrays the condition of Kalanganyar Village in Sidoarjo. With the existence of marine culture and the production of milkfish ponds, Kalanganyar Village has the potential to become a tourist destination. However, referring to the criteria of tourism village, Kalanganyar Village is very far from being categorized into tourism village. Nevertheless, the coastal natural resource and the wisdom of the local architecture can be developed into an asset of tourism village which will potentially improve the living standards of its people. The method used in this research are explorative and descriptive, which means exploring the natural physical potential, associated with existing urban elements, and the non-physical potential related to the socio-cultural community. The results, from mapping the authenticity of the form and character of the area in Kalanganyar Village, are described using synchronous reading (synchronic reading) and interpreted qualitatively. To describe the non-physical potential, the data obtained from the respondents' interviews were processed using simple quantification. The results of this study are then becoming the basis of development concept for Kalanganyar area as a tourist village, which includes the adjustment of spatial areas, regional morphology identification and building typologies based on the Coastal Architecture. These adjustments are performed in a schematic design and is expected to reflect the identity of the region.